2018
DOI: 10.1145/3274469
|View full text |Cite
|
Sign up to set email alerts
|

User Perceptions of Smart Home IoT Privacy

Abstract: Smart home Internet of Things (IoT) devices are rapidly increasing in popularity, with more households including Internet-connected devices that continuously monitor user activities. In this study, we conduct eleven semi-structured interviews with smart home owners, investigating their reasons for purchasing IoT devices, perceptions of smart home privacy risks, and actions taken to protect their privacy from those external to the home who create, manage, track, or regulate IoT devices and/or their data. We not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
188
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(213 citation statements)
references
References 49 publications
9
188
0
Order By: Relevance
“…Here, our findings demonstrate the importance of convenience of smart technology for its application in private households. This supports previous findings from Zheng and colleagues [8] who identified convenience as the driving factor in the usage of smart devices and substantiates the striving of manufacturers to create smart technology in a most comfortable way [11]. In their analysis, Yoon and Kim [12] revealed that convenience highly correlated with perceived usefulness of a smart device and that both factors are related to technology acceptance.…”
Section: <001 Accepted Page 1396supporting
confidence: 87%
See 2 more Smart Citations
“…Here, our findings demonstrate the importance of convenience of smart technology for its application in private households. This supports previous findings from Zheng and colleagues [8] who identified convenience as the driving factor in the usage of smart devices and substantiates the striving of manufacturers to create smart technology in a most comfortable way [11]. In their analysis, Yoon and Kim [12] revealed that convenience highly correlated with perceived usefulness of a smart device and that both factors are related to technology acceptance.…”
Section: <001 Accepted Page 1396supporting
confidence: 87%
“…Examples for smart, convenience providing technology are smart phones managing our daily habits, intelligent loudspeakers ordering new detergents on command or smart robotic vacuum cleaners saving effort and time. Zheng and colleagues [8] confirm convenience as the driving force behind the usage of smart devices.…”
Section: Privacy Calculus and The Benefit Of Conveniencementioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested in discussion of this paper that its findings are culturally limited; that the same issues would not be surfaced in the US or Asia, where people are less concerned with what happens to their data. Whether or not this is true is, of course, a matter for empirical investigation, though initial studies with regard to the IoT suggest that, while differences exist, matters are not so clear cut in the US at least(Zheng et al 2018). …”
mentioning
confidence: 99%
“…The study showed that homes can be unsafe spaces, in particular for people who are traditionally marginalised or considered to be at risk [23]. The latter are often reticent to take part in research related to connected devices, which makes manufacturers and the research community not aware of the harms those devices can cause when they end up being controlled by the wrong person [24,25]. Furthermore, those who share access to devices may also be a threat to others in the home [26].…”
mentioning
confidence: 99%